Constitutional Personae - Sunstein, Cass (Revista dos Estudantes de Direito da Universidade de Brasília, 2017)
American constitutional law is dominated by four Constitutional Personae, who can be identified by their inclinations, their temperaments, their sensibilities, and their self-presentations. Indeed, many constitutional debates consist of stylized disagreements among the leading Personae: Heroes, Soldiers, Burkeans, and Mutes. Earl Warren is the iconic Hero; Oliver Wendell Holmes, Jr. is the iconic Soldier; Felix Frankfurter is the iconic Burkean; Alexander Bickel speaks for the Mute. At different times and places, and under different constitutional provisions, liberals and conservatives can be Heroes, Soldiers, Burkeans, or Mutes. While the appeal of one or another Persona undoubtedly has psychological and social sources, the choice of the appropriate Persona, in particular cases, should be a product of the proper theory of constitutional interpretation, which must in turn be chosen on the basis of pragmatic judgments about the magnitude and number of errors.